1987
DOI: 10.1083/jcb.104.6.1623
|View full text |Cite
|
Sign up to set email alerts
|

Changes of nerve growth factor synthesis in nonneuronal cells in response to sciatic nerve transection.

Abstract: Abstract. The intact sciatic nerve contains levels of nerve growth factor (NGF) that are comparable to those of densely innervated peripheral target tissues of NGF-responsive (sympathetic and sensory) neurons. There, the high NGF levels are reflected by correspondingly high mRNA N~F levels. In the intact sciatic nerve, mRNA N~F levels were very low, thus indicating that the contribution of locally synthesized NGF by nonneuronal cells is small. However, after transection an increase of up to 15-fold in mRNA NC~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
404
1
8

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 987 publications
(429 citation statements)
references
References 34 publications
16
404
1
8
Order By: Relevance
“…Indeed, the local administration of CNTF after transection of the facial nerve in newborn rats virtually completely prevented the degeneration of the motoneuron cell bodies (93). Moreover, in adult animals, in spite of the reduction of the CNTF mRNA after transection of the sciatic nerve, the CNTF -assigned biological activity in the peripheral part of the sciatic nerve undergoing Wallerian degeneration was still about 1000 times higher than the amount of " reactively" enhanced synthesis of NGF by non neuronal sciatic cells 1 week after lesion (35,97,98). Certainly, CNTF is not the sole factor responsible for motoneuron regeneration in peripheral nerves.…”
Section: Thoenen Hughes and Sendtnermentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, the local administration of CNTF after transection of the facial nerve in newborn rats virtually completely prevented the degeneration of the motoneuron cell bodies (93). Moreover, in adult animals, in spite of the reduction of the CNTF mRNA after transection of the sciatic nerve, the CNTF -assigned biological activity in the peripheral part of the sciatic nerve undergoing Wallerian degeneration was still about 1000 times higher than the amount of " reactively" enhanced synthesis of NGF by non neuronal sciatic cells 1 week after lesion (35,97,98). Certainly, CNTF is not the sole factor responsible for motoneuron regeneration in peripheral nerves.…”
Section: Thoenen Hughes and Sendtnermentioning
confidence: 94%
“…The cloning of CNTF was the prerequisite for producing large quantities of recombinant CNTF (49,59,100) and for the determination of its developmental expression and cellular localization (20,27,86,94,97,100,101). These investigations demonstrated that CNTF is expressed postnatally in myelinating Schwann cells (27,86,97,100,101) and a subpopulation of type I astrocytes (20,101) in the CNS, that CNTF is a cytosolic molecule, and that the biological activity, e.g., in the adult sciatic nerve, is more than 10,000 _ times higher than that of (retrogradely) transported NGF in the rat sciatic nerve (35,97,98).…”
Section: Thoenen Hughes and Sendtnermentioning
confidence: 98%
“…NGF levels were increased (Heumann et al 1987) and NT-3 levels were decreased (Cai et al 1998) following sciatic crush injury. In addition, total neurotrophic support appears to be more important in the survival and maintenance of peripheral neurons than the influence of any one neurotrophin (Zhou et al 1999).…”
Section: Ngf and Nt-3 Protein In Peripheral Tissues Following Denervamentioning
confidence: 95%
“…This is reflected by the high ratio of NGF to mRNA NGF , in contrast to densely innervated peripheral organs, which bave NGF levels similar to those in the sciatic nerve . Tbe high NGF levels in the sciatic nerve result predominantly from NGF transported retrogradely from peripheral target tissues (Korsching and Thoenen , 1983b;Heumann et al, 1987). However, after transection of the sciatic nerve, local synthesis by nonneuronal cells increases up to 15-fold both proximally and distally to tbe transection site.…”
Section: Nonneuronal Ceusmentioning
confidence: 99%
“…However, the amount of tissue is too small to replace fully the interrupted supply from the periphery. In situ bybridization experiments demonstrated that after transection, all nonneuronal cells expressed mRNA NGF , and not just those ensheathing the NGF-responsive neurons Heumann et al , 1987). When pieces of rat sciatic were brought ioto culture, the mRNA NGF levels first increased to a maximum after 8 hr, and then dropped to lower levels between 12 and 24 hr, just as they do in vivo (Heumann er al.…”
Section: Nonneuronal Ceusmentioning
confidence: 99%